Protective Effect of Gabapentin on N-methyl-D-aspartate-Induced Excitotoxicity in Rat Hippocampal CA1 Neurons - Young-Sick Kim; Hyun-Kyung Chang; Jin-Woo Lee; Yun-Hee Sung; Sung-Eun Kim; Mal-Soon Shin; Jae-Woo Yi; Je-Hoon Park; Hong Kim; Chang-Ju Kim (Elsevier, 2009)
Gabapentin was developed as an anticonvulsant, but has also been used to alleviate hyperalgesia in neuropathic pain. In this study, the protective effect of gabapentin against N-methyl-D-aspartate (NMDA)-induced excitotoxicity in rat hippocampal CA1 neurons was investigated. Pre-treatment with gabapentin reduced the degree of neuronal damage induced by NMDA exposure in cultured hippocampal slices. Patch-clamp studies revealed that gabapentin significantly inhibited the NMDA receptor-activated ion current in dissociated hippocampal CA1 neurons, resulting in suppression of glutamate-induced neuronal injury. These results show that gabapentin may exert protective effects against glutamate-induced neuronal injury at least in part by inhibiting the NMDA receptor-activated ion current. Keywords:: gabapentin, N-methyl-D-aspartate, neuroprotection